2004
DOI: 10.1007/s00330-003-2085-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of parenchymal and vascular enhancement using saline flush and power injection for multiple-detector-row abdominal CT

Abstract: The aim of this study was to determine if a saline solution flush following low dose contrast material bolus improves parenchymal and vascular enhancement during abdominal multiple detector-row computed tomography (MDCT). Forty-one patients (24 men and 17 women; mean age 49 years, age range 27-86 years) underwent abdominal MDCT (collimation 4x5 mm, 15-mm table increment, reconstruction interval 5 mm, gantry rotation period 0.8 s) with a single- as well as with a double syringe power injector. Indication for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…By pushing this residual contrast medium into the central venous system, a saline flush could achieve a reduction of 12 mL [15] or 10% dose of contrast medium [3,11] with maintained arterial enhancement in the arterial phase. Other studies showed that saline flush increased the enhancement of coronary arteries [3] and aorta [10] by 10%. Saline flush could also reduce streak artifacts from the superior vena cava by washing out the excessive contrast medium [3,12] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…By pushing this residual contrast medium into the central venous system, a saline flush could achieve a reduction of 12 mL [15] or 10% dose of contrast medium [3,11] with maintained arterial enhancement in the arterial phase. Other studies showed that saline flush increased the enhancement of coronary arteries [3] and aorta [10] by 10%. Saline flush could also reduce streak artifacts from the superior vena cava by washing out the excessive contrast medium [3,12] .…”
Section: Discussionmentioning
confidence: 92%
“…Saline flush is also used in imaging the aorta [10][11][12] and carotid arteries [13] . A previous study showed that approximately 10 to 20 mL of contrast medium remained in the brachial vein or the superior vena cava without saline flush [14] .…”
Section: Discussionmentioning
confidence: 99%
“…The biphasic injection protocol was developed to overcome some of these shortcomings. Studies on the efficacy of biphasic injection protocol have demonstrated substantial improvement in image quality over the monophasic protocol, providing excellent coronary artery enhancement with less contrast-related streak artifacts in the SVC 22,23 . However, in many patients, the saline chaser bolus flushes contrast in the right cardiac chambers so effectively that it is unable to discern the internal structures (valve, papillary muscles, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…By pushing the tail of the injected contrast medium bolus, a saline chaser prevents pooling of contrast material in the peripheral venous compartment at the injection site and in the injection tubing, increasing the effectiveness of contrast material utilization [3]. The increased efficiency provided by a saline chaser can be exploited clinically to: (i) decrease the volume of contrast material (typically by 20-30 mL) without jeopardizing vascular and parenchymal enhancement [4][5][6][7][8][9], (ii) increase the magnitude of enhancement (by 5%-10%) using a standard dose of contrast material [10][11][12] or (iii), as recently advocated [13], attain durable and uniform peak enhancement during the entire CT acquisition. However, although the advantages of a saline chaser for optimizing CT contrast enhancement are widely accepted, disagreement remains over the most effective injection protocol for the administration of saline [14][15][16].…”
Section: Introductionmentioning
confidence: 99%